Internal multi-centennial variability of the Atlantic Meridional Overturning Circulation simulated by EC-Earth3 - Meccia V. L.; Fuentes-Franco R.; Davini P.; Bellomo K.; Fabiano F.; Yang S.; von Hardenberg J. (Climate Dynamics, 2022)
We report a multi-centennial oscillation of the Atlantic Meridional Overturning Circulation (AMOC) simulated by the EC-Earth3 climate model under the pre-industrial climate. This oscillation has an amplitude of ~ 6 Sv and a period of ~ 150 years and significantly impacts the atmosphere. We find that it is a self-sustained low-frequency internal variability, driven by the accumulation of salinity anomalies in the Arctic and their release into the North Atlantic, affecting the water column stability and the deep convection. Sea ice plays a major role in creating the salinity anomaly in the Arctic, while the anomalous Arctic oceanic circulation, which drives the exchange of liquid freshwater between the Arctic and the open ocean, is the main responsible for its southward propagation. Interestingly, EC-Earth3 simulations with increased greenhouse concentrations, and therefore under a warmer climate, do not exhibit these strong AMOC fluctuations. We hypothesize that in a quasi-equilibrium climate with a global air surface temperature 4.5° higher than the pre-industrial period, the low amount of sea ice in the high latitudes of the North Atlantic is no longer able to trigger the mechanism.